Repeated Rhyolite Eruption From Heterogeneous Hot Zones Embedded Within a Cool, Shallow Magma Reservoir. Issue 3 (25th March 2019) - Andersen, Nathan L.; Singer, Brad S.; Coble, Matthew A.
Abstract: Despite the hazard posed by explosive silicic eruptions, the magma storage conditions and dynamics that precede these events remain controversial. The Laguna del Maule volcanic field, central Chile, is an exceptional example of postglacial (younger than ca. 20, 000 years) rhyolite volcanism and sustained unrest driven by a large, shallow, active silicic magma system. New zircon petrochronologic data reveal that compositionally distinct domains developed concurrently within the Laguna del Maule magma reservoir, which produced two episodes of concentrated rhyolitic eruptions at 23–19 and 8–2 ka. Zircon crystallization ages record 160 kyr of magma emplacement resulting in a several hundreds of cubic kilometers reservoir that has been imaged geophysically. The average magma emplacement rate inferred from the zircon geochronology and tomographically defined magma volume is consistent with those required by thermal models to maintain a shallow silicic system. Ti‐in‐zircon temperatures of crystal cores and rims and hiatuses in crystal growth indicates most of this volume persisted in a near‐solidus state. However, consistent patterns of trace element zoning in crystal interiors and crystallization rates derived from a model of diffusion‐limited zircon growth suggest the erupted rhyolite magma batches originated from long‐lived hot zones of extractable mush embedded within the larger, cool reservoir of rigid mush. These contrasting, coeval magma storage conditions obviate a simple hot versus cold storage dichotomy for large silicic magma systems. Plain Language Summary: Elucidating the magma storage conditions and processes that preceded prehistoric eruptions is critical to improving the interpretation of volcano monitoring data. An important, yet controversial, consideration is if long‐term magma storage is dominated by cold, mineral‐rich, and uneruptible conditions or if warm, mobile magma bodies can persist for thousands of years. The mineral zircon is indispensable for reconstructing pre‐eruption behavior because it records the host magma composition and temperature and may be dated at the intracrystal scale. We present ages and chemical compositions of zircon crystals from the Laguna del Maule volcanic field (LdM), located in central Chile. LdM has experienced more than 2 m of uplift since 2007 within a ring of volcanic vents that have erupted repeatedly over the last 20, 000 years. The LdM magma reservoir grew over 34, 000 to 160, 000 years and persisted largely in a cool, crystal‐rich state. However, the erupted magma was derived from hot zones within the larger reservoir that endured throughout this time. These heterogeneous magma storage conditions preclude a simple conceptual framework of magma storage and highlight the need for future integration of forensic investigations of volcanic deposits with models of three‐phase (crystals, melt, and fluid) magma reservoirs dynamics. Key Points: Zircon petrochronology records the accumulation of a large, shallow, heterogeneous silicic magma system Eruptible rhyolite melt was derived from distinct, hot magma mush bodies that resided within a cool, crystalline magma reservoir Composition and thermal variability in time and space is increasingly recognized in shallow silicic magma systems